2016
DOI: 10.1039/c6dt02669a
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis and structures of 1,1′-bis(sulfonyl)ferrocene derivatives

Abstract: A series of 1,1′-bis(sulfonyl)ferrocene compounds were produced via the 1,1′-bis(sulfonate)ferrocene ammonium salt. This compound can be readily converted to 1,1′ bis(sulfonylchloride)ferrocene. Varying stoichiometry and reaction times, both mono- and bis-sulfonamide derivatives can be synthesized. All new compounds presented in this report have been structurally characterized. The structures of the bis-sulfonamide systems are similar to the well-studied bis(amide) ferrocene compounds. Intermolecular hydrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 41 publications
3
23
0
Order By: Relevance
“…As we were investigating the amino acid chemistry of compound 1 , we observed an unusual reaction with glycine methyl ester. For most primary amines, we observe either the formation of mono or bi‐functionalized ferrocene sulfonamides . However in the case of glycine methyl ester, we observed the formation of a [3]ferrocenophane, compound 5 .…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…As we were investigating the amino acid chemistry of compound 1 , we observed an unusual reaction with glycine methyl ester. For most primary amines, we observe either the formation of mono or bi‐functionalized ferrocene sulfonamides . However in the case of glycine methyl ester, we observed the formation of a [3]ferrocenophane, compound 5 .…”
Section: Resultsmentioning
confidence: 80%
“…1,1’‐Bis(sulfonylchloride) ferrocene 1 can be readily generated in three steps from ferrocene via reaction with chlorosulfonic acid, isolation as the ammonium salt, and then reaction with PCl 5 . Previously, we have shown that 1 can be used to generate both mono‐ and bis(sulfonamide) derivatives . The sulfonyl chloride is useful in that it exhibits selectivity in reactivity with amines under wet (i. e. non‐dried) conditions, however reactions with amines frequently requires higher temperatures or extended reaction times.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among transition metal‐based compounds, ferrocenes have many notable properties as RFB components, ranging from their relative low cost and ease of synthesis to their stabilities and electrochemical reversibility in a variety of media. As part of our continuing investigations into the synthetic modification of ferrocene, we have produced an “all ferrocene” salt (compound 1 , Figure ) comprised of two (ferrocenylmethyl)trimethylammonium cations and a 1,1’‐bis(sulfonate)ferrocene dianion. We observed that this compound exhibits switching of the redox potentials between the cation and anion depending on solution conditions, completely reversing the order in which the cation and anion are oxidized.…”
Section: Figurementioning
confidence: 99%
“…Starting from ferrocenyl alcohols FcCH (OH)R and ethyl esters of glycine and β‐alanine under acidic catalysis in aqueous organic medium the corresponding products were obtained . Recently Ziegler and co‐workers elaborated new synthetic route to ferrocene complexes of such type using a sulfonamide linking strategy . Ferrocene‐based pyrazole‐containing amino acids were successfully prepared by Vukićević and co‐workers, and evaluated as promising antitumor agents .…”
Section: Resultsmentioning
confidence: 99%